The GIP/GIPR axis is functionally linked to GH-secretion increase in a significant proportion of gsp− somatotropinomas. Issue 5 (May 2017) - Regazzo, D; Losa, M; Albiger, N M; Terreni, M R; Vazza, G; Ceccato, F; Emanuelli, E; Denaro, L; Scaroni, C; Occhi, G
Abstract : Objective: Glucose-dependent insulinotropic polypeptide receptor ( GIPR ) overexpression has been recently described in a proportion of gsp − somatotropinomas and suggested to be associated with the paradoxical increase of GH (GH-PI) during an oral glucose load. Design and methods: This study was aimed at linking the GIP/GIPR pathway to GH secretion in 25 somatotropinomas-derived primary cultures and correlating molecular with clinical features in acromegalic patients. Given the impairment of the GIP/GIPR axis in acromegaly, an additional aim was to assess the effect of GH/IGF-1 stimulation on GIP expression in the enteroendocrine cell line STC-1. Results: Nearly 80% of GIPR -expressing somatotropinomas, all of them negative for gsp mutations, show increased GH secretion upon GIP stimulation, higher sensitivity to Forskolin but not to somatostatin analogs. Besides increased frequency of GH-PI, GIPR overexpression does not appear to affect acromegalic patients' clinical features. In STC-1 cells transfected with GIP promoter-driven luciferase vector, IGF-1 but not GH induced dose-dependent increase in luciferase activity. Conclusions: We demonstrate that GIPR mediates the GH-PI in a significant proportion of gsp − acromegalic patients. In these cases, the stimulatory effect of IGF-1 on GIP promoter support the hypothesis of a functional GH/IGF-1/GIP axis. Further studies based on larger cohorts and the development of a stable transgenic model with inducible GIPR overexpression targeted to pituitary somatotroph lineage will be mandatory to establish the real role of GIPR in the pathogenesis of somatotropinomas.